Central catalytic domain of BRAP (RNF52) recognizes the types of ubiquitin chains and utilizes oligo-ubiquitin for ubiquitylation - Shoji, Shisako (Biochem J, 2017)
Really interesting new gene (RING)-finger protein 52 (RNF52), an E3 ubiquitin ligase, is found in eukaryotes from yeast to humans. Human RNF52 is known as breast cancer type 1 susceptibility protein (BRCA1)-associated protein 2 (BRAP or BRAP2). The central catalytic domain of BRAP comprises four subdomains: nucleotide-binding α/β plait (NBP), really interesting new gene (RING) zinc finger, ubiquitin-specific protease (UBP)-like zinc finger (ZfUBP), and coiled-coil (CC). This domain architecture is conserved in RNF52 orthologs; however, the domain's function in the ubiquitin system has not been delineated. In the present study, we discovered that the RNF52 domain, comprising NBP–RING–ZfUBP–CC, binds to ubiquitin chains (oligo-ubiquitin) but not to the ubiquitin monomers, and can utilize various ubiquitin chains for ubiquitylation and auto-ubiquitylation. The RNF52 domain preferentially bound to M1- and K63-linked di-ubiquitin chains, weakly to K27-linked chains, but not to K6-, K11-, or K48-linked chains. The binding preferences of the RNF52 domain for ubiquitin-linkage types corresponded to ubiquitin usage in the ubiquitylation reaction, except for K11-, K29-, and K33-linked chains. Additionally, the RNF52 domain directly ligated the intact M1-linked, tri-, and tetra-ubiquitin chains and recognized the structural alterations caused by the phosphomimetic mutation of these ubiquitin chains. Full-length BRAP had nearly the same specificity for the ubiquitin-chain types as the RNF52 domain alone. Mass spectrometry analysis of oligomeric ubiquitylation products, mediated by the RNF52 domain, revealed that the ubiquitin-linkage types and auto-ubiquitylation sites depend on the length of ubiquitin chains. Here, we propose a model for the oligomeric ubiquitylation process, controlled by the RNF52 domain, which is not a sequential assembly process involving monomers.